Clinical efficacy and safety of combined anti-BCMA and anti-CD19 CAR-T cell therapy for relapsed/refractory multiple myeloma: a systematic review and meta-analysis - Xu, Han; Guan, Chaoyang; Xu, Peipei; Zhou, Dongming; Xu, Yong; Chen, Bing; Bai, Hua (Frontiers in Oncology, 2024)
Background The low rates of durable response against relapsed/refractory multiple myeloma (RRMM) in recent studies prompt that chimeric antigen receptor (CAR)-T cell therapies are yet to be optimized. The combined anti-BCMA and anti-CD19 CAR-T cell therapy showed high clinical efficacy in several clinical trials for RRMM. We here conducted a meta-analysis to confirm its efficacy and safety. Methods We collected data from Embase, Web of Science, PubMed, CNKI, Wanfang and Cochrane databases up to April 2023. We extracted and evaluated data related to the efficacy and safety of combined anti-BCMA and anti-CD19 CAR-T cell therapies in RRMM patients. The data was then analyzed using RevMan5.4 and StataSE-64 software. PROSPERO number was CRD42023455002. Results Our meta-analysis included 12 relevant clinical trials involving 347 RRMM patients who were treated with combined anti-BCMA and anti-CD19 CAR-T cell therapies. For efficacy assessment, the pooled overall response rate (ORR) was 94% (95% CI: 91%-98%), the complete response rate (CRR) was 50% (95% CI: 29%-71%), and the minimal residual disease (MRD) negativity rate within responders was 73% (95% CI: 66%-80%). In terms of safety, the pooled all-grade cytokine release syndrome (CRS) rate was 98% (95% CI: 97%-100%), grade≥3 CRS rate was 9% (95% CI: 4%-14%), and the incidence of neurotoxicity was 8% (95% CI: 4%-11%). Of hematologic toxicity, neutropenia was 82% (95% CI: 75%-89%), anemia was 71% (95% CI: 53%-90%), thrombocytopenia was 67% (95% CI: 40%-93%) and infection was 42% (95% CI: 9%-76%). The median progression-free survival (PFS) was 12.97 months (95% CI: 6.02-19.91), and the median overall survival (OS) was 26.63 months (95% CI: 8.14-45.11). Conclusions As a novel immunotherapy strategy with great potential, the combined anti-BCMA and anti-CD19 CAR-T cell therapy showed high efficacy in RRMM, but its safety needs further improvement. This meta-analysis suggests possible optimization of combined CAR-T therapy. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023455002.